Dimensions, discourses and differences: trainees conceptualising health care leadership and followership. Issue 12 (December 2015) - Gordon, Lisi J; Rees, Charlotte E; Ker, Jean S; Cleland, Jennifer
Abstract : Context: As doctors in all specialties are expected to undertake leadership within health care organisations, leadership development has become an inherent part of medical education. Whereas the leadership literature within medical education remains mostly focused on individual, hierarchical leadership, contemporary theory posits leadership as a group process, which should be distributed across all levels of health care organisation. This gap between theory and practice indicates that there is a need to understand what leadership and followership mean to medical trainees working in today's interprofessional health care workplace. Methods: Epistemologically grounded in social constructionism, this research involved 19 individual and 11 group interviews with 65 UK medical trainees across all stages of training and a range of specialties. Semi‐structured interviewing techniques were employed to capture medical trainees' conceptualisations of leadership and followership. Interviews were audiotaped, transcribed verbatim and analysed using thematic framework analysis to identify leadership and followership dimensions which were subsequently mapped onto leadership discourses found in the literature. Results: Although diversity existed in terms of medical trainees' understandings of leadership and followership, unsophisticated conceptualisations focusing on individual behaviours, hierarchy and personality were commonplace in trainees' understandings. This indicated the dominance of an individualist discourse. Patterns in understandings across all stages of training and specialties, and whether definitions were solicited or unsolicited, illustrated that context heavily influenced trainees' conceptualisations of leadership and followership. Conclusions: Our findings suggest that UK trainees typically hold traditional understandings of leadership and followership, which are clearly influenced by the organisational structures in which they work. Although education may change these understandings to some extent, changes in leadership practices to reflect contemporary theory are unlikely to be sustained if leadership experiences in the workplace continue to be based on individualist models. Abstract : Discuss ideas arising from the article atwww.mededuc.com discuss.